Diseño e implementación de un plan estratégico de Talento Humano para fomentar el compromiso del personal de la empresa Hormiconstrucciones Cía. Ltda. - Ortega Méndez, Silvia Eugenia (2025)
This study was carried out in the private company Hormiconstrucciones Cía. Ltda., and its purpose is to design and implement a strategic human talent plan to promote the commitment of the company's staff. Considering the importance of staff having an adequate organizational climate for optimal and adequate productivity, a diagnosis of the organization was carried out to propose appropriate strategies to improve the human component. The organizational climate was analyzed using the Likert scale that covers eight dimensions: working conditions, interpersonal relationships, internal communication, organizational structure, professional training, recognition and promotion, motivation and satisfaction, and psychosocial. With the information collected in the diagnosis of the current situation, a SWOT matrix was developed, which allowed proposing strategies that allow the company to have a model to promote the commitment of the staff of the company Hormiconstrucciones Cía. Ltda.